Crystallization- and morphology-tunable Fe3O4@C core–shell composites decorated on carbon nanotube skeleton with tailorable electromagnetic wave absorption behavior. (9th November 2020) - Zhao, Yongpeng; Zhang, Hao; Cong, Tianze; Huang, Hui; Muhammad, Javid; Zuo, Xueqing; Guo, Yuan; Pan, Lujun
Abstract: Herein, a scalable method is developed to fabricate carbon nanotube (CNT)/Fe3 O4 @C composites, in which the crystallization and morphology of the carbon shell on the surface of Fe3 O4 nanoparticles can be controlled by manipulating the synthesis conditions of chemical vapor deposition technology. Owing to the synergic dissipation effect of the core–shell structure, as well as the excellent conductive loss induced by the CNT skeleton, the CNT/Fe3 O4 @C composite shows a minimum reflection loss of −50.1 dB at 9.7 GHz and an effective bandwidth of 4.6 GHz. This study provides new insight into preparing core–shell-structured microwave absorbers with excellent performance.